LIMBS REAMPUTATIONS IN MILITARY PERSONNEL INJURED IN THE AREA OF THE ANTITERRORIST OPERATION IN EAST UKRAINE - Bespalenko, А.А.; Buryanov, А.А.; Tsema, Ie.V.; Dinets, A.V. (The Ukrainian Scientific Medical Youth Journal, 2018)
The aim – to identify and analyze causes for reamputations in military personnel with limb amputations due to ATO in East Ukraine. Patients and methods. All military personnel of the AFU within ATO was eligible for the study with diagnosis of limb amputations in the period from 01.06.2014 to 30.06.2016, and which were treated in hospitals of the Ministry of Defense of Ukraine. Among 7091 patients with injuries, 152 patients with limb amputations were identified.Results and discussion. Out of 152 patients, 25 (16%) underwent limbs reamputation, whereas 127 (84%) patients underwent amputation once. Patients in the study groups did not differ in age. Amputation was performed on the upper limb in 41 (32%) in the group of patients with amputations, which is significantly higher as compared to 2 (8%) patients in the reamputation group (p = 0.014). Analyses the level of amputations of the upper extremity showed no difference in the parameters. In 23 (92%) patients in the group with reamputation amputation of the lower limbs were diagnosed significantly more often as compared to 86 (68%) patients in the amputation group (p = 0.014). Analyses of the level of amputation of the lower extremity revealed that almost 3 times more often amputation was performed at the level of the ankle in the group of patients with reputations - 8 (32%) patients, as compared to 15 (12%) patients in the amputation group (p = 0.03). However, linear regression did not show a significant difference of these parameters in reamputations. Amputation of one upper extremity in the reamputation group was diagnosed 7 times less frequent - 1(4%) patient less often than in the amputation group - 37(29%) patients (p = 0.005).Conclusions: The results of the study of the injured in a hybrid war indicate that reamputations are more often associated with amputations at the level of the upper limb, but are less often diagnosed in patients with amputation of the lower extremity. Reamputations are more often performed with trauma of one limb. Clinical features in patients injured in the ATO zone in the East Ukraine demonstrate the frequency and characteristics of re-arrests that are different from other armed conflicts.